Laboratory information management system study & development of LIMS web platform application for CTCV - Coimbra - Baldaniya, Hitesh D (2020)
The World Wide Web not only changes the process but also improves the user experience. Also, it dramatically changes how the computer software is built. This profound evolution of software development has caused developers in the software industry to change their way of developing software. In this project, the Laboratory Information Management System (LIMS) for Staff and Users of small business have been designed and developed using Throwaway Prototyping methodology with the web architecture. Different types of development platforms are available in the market to develop this application, but as per the company requirements, this application was developed with the .net framework. This web application allows us to access application data on different devices like a tablet, a desktop, a smartphone from the remote location all over the world. The main feature of this application offers to monitor the application activity like which activity was performed by the user with the corresponding date, time and short description. Therefore, this software uses an industry standard relational database management system (RDBMS) combined with a platform-independent web browser interface for data entry and the retrieval. (The 3-tier technology) The laboratory workflow steps facilitate the management and tracking of all test and test results, which ensures that the right information is available at the right time to a right person. This system will produce an efficient process in the laboratory which leads to faster work, fewer errors, and smoother workflow for an organization. Keywords Industry